The Analysis of Factors Influencing Financial Technology Usage in Higher Education - Vhalery, Rendika; Leksono, Ari Wahyu; Anggresta, Vella (Fakultas Ekonomi, Universitas Negeri Semarang, 2020)
This study aims to analyze and to shape the factors that influence the use of financial technology, especially among students, because recently the financial technology usage among students increased slightly in the previous year. This increase was influenced by several factors that have not been classified. The population consisted of 1,229 students of the Indraprasta University PGRI Jakarta, with 273 students as the sample obtained using simple random sampling. Techniques of data collection used a questionnaire with a Likert scale consisting of seven points. Techniques of data analysis used factor analysis from software Statistical Package for the Social Science version 24.0. The results of the factor analysis show that eight factors are formed from several variables, with a contribution of 65.368%. While 34,632% is explained by other not examined factors, these factors consist of security, product offered, access and profit, loyalty, information, facility, demand and quality. For future research, it needs to test and analyze factors formed to add references of science and technology, especially in the field of financial technology.